2014
DOI: 10.3109/10826084.2014.962048
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use and Sexual Behaviors Among MSM in China

Abstract: It is crucial to increase research and include Chinese MSM and their drug use in the Chinese policy conversation. These data suggest that drug use and sexual behaviors after drug use among Chinese MSM differ widely based upon selling sex and separate intervention strategies may be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…On the other hand, MBs in China often sell sex to both males and females to increase their income [ 24 ]. MBs have become one of the emerging high risk subgroups of MSM communities in recent years [ 60 – 62 ], so higher rate of commercial sex in MSMW was associated with HIV transmission. The current systematic review also estimated that MSMW were 2.1 and 3.0 times more likely to engage in alcohol use than MSMO.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MBs in China often sell sex to both males and females to increase their income [ 24 ]. MBs have become one of the emerging high risk subgroups of MSM communities in recent years [ 60 – 62 ], so higher rate of commercial sex in MSMW was associated with HIV transmission. The current systematic review also estimated that MSMW were 2.1 and 3.0 times more likely to engage in alcohol use than MSMO.…”
Section: Discussionmentioning
confidence: 99%
“…This underscores urgent needs of joint intervention efforts for drug use and risky sexual behaviors among MSM in China. Furthermore, given that MBs use drugs more often and have sex more often after using drugs than general MSM (Chow et al, 2012; Nehl et al, 2014), such intervention efforts should be oriented differentially for MBs and general MSM.…”
Section: Discussionmentioning
confidence: 99%
“…IDU is rare among Chinese MSM (Nehl et al, 2015); however, use of alcohol and recreational drugs is common (Lu et al, 2013; Xu et al, 2014a,b). Alcohol and recreational drug use may lead to sexual risk-taking behaviors (Jia et al, 2010; Li et al, 2012; Santos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While the association between club drug use and risky sexual behavior has been established, the specific type of drugs and their link with risky sexual behavior are geographically different around the globe (Van Tieu and Koblin, 2009). Previous studies among Chinese MSM have shown that certain club drugs are more popular than others, especially inhalant nitrites (poppers) (Nehl et al, 2015; Xu et al, 2014a,b). …”
Section: Introductionmentioning
confidence: 99%